Adoption of M- Wallet: A Way Ahead (Trinity Journal of Management, IT & Media (TJMITM), 2017)
Demonetization in India has given a boost to digital payments  and has encouraged people to go cashless. The government of  India in tandem with RBI has been setting out plans to encourage  electronic payments that enable India to move towards cashless  economy, with the aim to curb the flow of black money and  circulation of counterfeit currency. With the advent of technology,  consumers have enormous options of making payments through  debit cards, credit cards and internet banking, which facilitates  the payment for the transactions more convenient and  accessible. With the increased penetration of smart phones  usage amongst Indians, mobile payments is gaining grounds in  India. Besides being used to access internet, people use smart  phones to store receipts, business cards and bills. But of late  smart phones function as leather wallets, commonly known as  “mobile wallet” or M-Wallet. M-Wallet services help the smart  phones users to transfer money from bank to m-wallet and use  that money to pay for services such as shopping, tickets,  recharging and bill payments. M-Wallet not only offers  convenience and security but also offers affordability over other  modes of payment especially when transferring of money is  involved. India is witnessing growth of M-wallet service providers  like Paytm, Mobikwik, Vodafone m-pesa and others. The  purpose of this study is to analyze and find out the status of  adoption of M-wallet services and to find out the gender and age  based variance in adoption of M-wallet modes of cashless  payments/ transactions. The findings of this study suggest that  adoption of M-wallet has increased due to three main factors  convenience, ease of use, compulsion after demonetization. It  has been found that there is gender and age based variance in  the adoption of M-wallet.
Keywords: Demonetization; Cashless; Electronic payments; Mobile- wallet